2018
DOI: 10.1016/j.asr.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin–Helmholtz instability in a twisting solar polar coronal hole jet observed by SDO/AIA

Abstract: We investigate the conditions under which the fluting (m = 2), m = 3, and m = 12 magnetohydrodynamic (MHD) modes in a uniformly twisted flux tube moving along its axis become unstable in order to model the Kelvin-Helmholtz (KH) instability in a twisting solar coronal hole jet near the northern pole of the Sun. We employed the dispersion relations of MHD modes derived from the linearized MHD equations. We assumed real wavenumbers and complex angular wave frequencies, namely complex wave phse velocities. The dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…During its evolution in 304 Å we found the blob structures at the jet boundary. These blobs could be due to the KHI as reported in previous observations (see, for example Zhelyazkov et al, 2018a). At the jet initiation/base site, we observed the coronal hole bright points.…”
Section: Kelvin-helmholtz Instability In a Blowout Polar Coronal Holesupporting
confidence: 86%
See 2 more Smart Citations
“…During its evolution in 304 Å we found the blob structures at the jet boundary. These blobs could be due to the KHI as reported in previous observations (see, for example Zhelyazkov et al, 2018a). At the jet initiation/base site, we observed the coronal hole bright points.…”
Section: Kelvin-helmholtz Instability In a Blowout Polar Coronal Holesupporting
confidence: 86%
“…In this article, we also corrected the total pressure balance equation used in Zhelyazkov et al, 2018a andChandra, 2018b, which turns out to be erroneous. The true total balance equation is given by equation (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be found on the interface between an erupting/dimming region and the surrounding corona in AIA EUV passbands (Ofman & Thompson 2011). The vortex-like structures of KHIs were also detected on the boundary of a filament which embedded in a CME (Möstl et al 2013) or along the boundary of a twisting solar polar coronal hole jet (Shen et al 2011b;Zhelyazkov et al 2018) at lower temper-ature, such as AIA 304Å. Beside the SDO/AIA observations, Feng et al (2013) reported a KHI in a coronal streamer which detected by the Solar and Heliospheric Observatory (SOHO).…”
Section: Introductionmentioning
confidence: 99%
“…Rossby waves and their coupling with solar activity are analysed (Zaqarashvili and Gurgenashvili 2018). Solar magnetic tubes, their effect on solar wind turbulence and its heating is studied (Zhelyazkov et al 2018). Outer corona dynamics in radio waves are also analyzed (Pylaev et al 2017).…”
Section: Research Topicsmentioning
confidence: 99%